Novel regulatory mechanism of establishment genes of conjugative plasmids. Issue 22 (31st October 2018) - Val-Calvo, Jorge; Luque-Ortega, Juan R; Crespo, Isidro; Miguel-Arribas, Andrés; Abia, David; Sánchez-Hevia, Dione L; Serrano, Ester; Gago-Córdoba, César; Ares, Saúl; Alfonso, Carlos; Rojo, Fernando; Wu, Ling J; et al.
Abstract: The principal route for dissemination of antibiotic resistance genes is conjugation by which a conjugative DNA element is transferred from a donor to a recipient cell. Conjugative elements contain genes that are important for their establishment in the new host, for instance by counteracting the host defense mechanisms acting against incoming foreign DNA. Little is known about these establishment genes and how they are regulated. Here, we deciphered the regulation mechanism of possible establishment genes of plasmid p576 from the Gram-positive bacterium Bacillus pumilus . Unlike the ssDNA promoters described for some conjugative plasmids, the four promoters of these p576 genes are repressed by a repressor protein, which we named Reg576 . Reg576 also regulates its own expression. After transfer of the DNA, these genes are de-repressed for a period of time until sufficient Reg576 is synthesized to repress the promoters again. Complementary in vivo and in vitro analyses showed that different operator configurations in the promoter regions of these genes lead to different responses to Reg576 . Each operator is bound with extreme cooperativity by two Reg576 -dimers. The X-ray structure revealed that Reg576 has a Ribbon-Helix-Helix core and provided important insights into the high cooperativity of DNA recognition.